Joint signal alignment precoding and physical network coding for heterogeneous networks - Ali, Syed Saqlain
Mobile traffic in cellular based networks is increasing exponentially, mainly due to the use of data intensive services like video. One effective way to cope with these demands is to reduce the cell-size by deploying small-cells along the coverage area of the current macro-cell system. The deployment of small-cells significantly improves the indoor coverage. Nevertheless, as additional spectrum licenses are difficult and expensive to acquire, it is expected that the macro and small-cells will coexist under the same spectrum. The coexistence of the two systems results in cross-tier/inter-system interference. In this context, we consider the application of joint signal alignment (SA) and physical network coding (PNC) for the uplink of heterogeneous networks, in order to cancel the interference generated from small-cells at the macro-cell user terminal. The joint design of SA and PNC allows to serve more users than the case where only PNC or interference alignment (IA) is employed individually. We compare our proposed joint SA-PNC schemes with the recently designed IA based techniques for the uplink heterogeneous systems. Simulation results show that the proposed SA-PNC is quite efficient to remove the inter-tier/system interference while allowing to increase the overall data rate, by serving more users, as compared with the IA based methods